The Exemplary Woman in “Movimiento perpetuo,” by Augusto Monterroso - Robles Murillo, Keylor (2020)
An analysis is conducted on the representation of model women in the short story “Movimiento perpetuo,” by Augusto Monterroso. The study is composed of three phases: a critical apparatus to approach the text, the analysis itself, and an explanation and interpretation of sexism. This shows how literature can reproduce discourses legitimized in systems of oppression. In this case, a description is provided of the way the author represents the female character based on the features of the exemplary woman: submission, subjection and obedience.